Money laundering as a major risk to the stability of the banking industry - Kot, Marek (Pranie pieniędzy jako istotne zagrożenie stabilności sektora bankowego, 2021)
This paper presents important and pending risks to the stability of the banking industry arising from the impact of money-laundering practices. The major focus is placed upon the proper organization of the terms typically employed in relation to the issue under study, supported by critical literature analyses and complete with an attempted evaluation of the potential effects of money-laundering processes. The paper provides an overview of the issue at hand without aspiring to form any exhaustive judgements. The marked dynamics of changes, both in the banking segment and its immediate environment, requires constant evaluation and observation, and this postulate applies also to processes associated with money-laundering. The wealth of the presented data may serve as the basis for further research of analytical approaches to the study of money-laundering practices.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 4, s. 77-93
Keywords: money laundering; stability; banking industry; economy; financial crime; pranie pieniędzy; stabilność; sektor bankowy; gospodarka; przestępstwa finansowe